The circadian system modulates the cortisol awakening response in humans - Bowles, Nicole P.; Thosar, Saurabh S.; Butler, Matthew P.; Clemons, Noal A.; Robinson, LaTroy D.; Ordaz, Omar H.; Herzig, Maya X.; McHill, Andrew W.; Rice, Sean P. M.; Emens, Jonathan; Shea, Steven A. (Frontiers in Neuroscience, 2022)
Background: In humans, circulating cortisol usually peaks 30-60 minutes after awakening from nocturnal sleep, commonly referred to as the cortisol awakening response (CAR). Despite prior reports that the CAR is reduced or absent following daytime sleep, the mechanisms underlying this attenuated response remain elusive. To address this gap, we examined the extent to which the CAR is influenced by the circadian system, independent of behaviors including sleep. Methods: We examined the CAR in 34 adults (20 female) using two complementary multiday in-laboratory circadian protocols performed in dim light, throughout which behavioral factors were uniformly distributed across the 24-hour circadian cycle. Protocol 1 consisted of 10 identical consecutive 5-hour 20-minute sleep/wake cycles and protocol 2 consisted of 5 identical consecutive 18-hour sleep/wake cycles. Salivary melatonin was used as the circadian phase marker (0° = dim light melatonin onset). During each sleep/wake cycle, salivary cortisol was measured upon scheduled awakening and 50-minutes later, with the change in cortisol defined as the CAR. Cosinor analyses were used to detect any significant circadian rhythmicity in the CAR. In secondary analyses, we adjusted the models for time awake before lights on, total sleep time, percent of rapid eye movement (REM) sleep, and percent of non-rapid eye movement (NREM) sleep. Results: Both protocols revealed a similar circadian rhythm in the CAR, with peaks occurring at a circadian phase corresponding to 3:40-3:45 AM, with no detectable CAR during the circadian phases corresponding to the afternoon. In addition to the sinusoidal component of the circadian rhythm, total sleep time was also associated with the CAR for protocol 1. The percent of sleep spent in REM or NREM sleep were not associated with the CAR in either protocol. Conclusion: Our results show that the CAR exhibits a robust circadian rhythm that persists even after adjusting for prior sleep. These findings may have implications for shift workers whose daytime sleep is likely to result in a blunted CAR. Presuming that the CAR optimizes physiological responses to the anticipated stressors related to awakening, a blunted CAR in shift workers may result in diminished responses to stressors.